Effect of Polydextrose on the Growth of Pediococcus pentosaceus as Well as Lactic Acid and Bacteriocin-like Inhibitory Substances (BLIS) Production - Maria Carolina Wanderley Porto; Pamela Oliveira de Souza de Azevedo; Felipe Rebello Lourenço; Attilio Converti; Michele Vitolo; Ricardo Pinheiro de Souza Oliveira (Microorganisms, 2022)
Pediococcus pentosaceus was cultivated in MRS medium supplemented or not with polydextrose under different conditions in order to evaluate its effect on cell growth, lactic acid and bacteriocin-like inhibitory substance (BLIS) production. Independent variables were pH (4.0, 5.0, 6.0), rotational speed (50, 100, 150 rpm), polydextrose concentration (0.5, 1.0, 1.5%) and temperature (25, 30, 35 °C), while cell concentration and productivity after 24 h, maximum specific growth rate, specific rate of substrate (glucose) consumption, volumetric and specific lactic acid productivities, yields of biomass and lactic acid on consumed substrate were the dependent. The maximum cell concentration (10.24 ± 0.16 gX L−1) and productivity (0.42 ± 0.01 gX L−1 h−1) were achieved at pH 6.0, 35 °C, 150 rpm using 1.5% polydextrose, while the maximum specific growth rate (0.99 ± 0.01 h−1) and yield of biomass (2.96 ± 0.34 gX gS−1) were achieved at the same pH and polydextrose concentration, but at 25 °C and 50 rpm. The specific substrate consumption rate (0.09 ± 0.02 gS gX−1 h−1) and the volumetric lactic acid productivity (0.44 ± 0.02 gP L−1 h−1) were maximized at pH 6.0, 35 °C, 50 rpm and 0.5% polydextrose. BLIS produced in this last run displayed the highest antibacterial activity against Escherichia coli, while the same activity was displayed against Enterococcus faecium using 1.5% polydextrose. These results appear to be quite promising in view of possible production of this BLIS as an antibacterial agent in the food industry.